A new cave-dwelling species of Charinus (Amblypygi: Charinidae) from northern Brazil - Souza, Priscila Emanuela De; Reis-Venâncio, Paulo César; Torres, Richard A.; Ferreira, Rodrigo Lopes (Zootaxa, 2024)
We present the description and illustration of a new species within the genus Charinus Simon, 1892, discovered in a cave located in the state of Tocantins, situated in the northern region of Brazil. Charinus tocantinensis sp. nov., can be distinguished from its congeners by the following combination of distinctive characters: pedipalp femur with four dorsal spines and four ventral spines; well-developed median eyes and median ocular tubercle; female gonopods sucker-like, slightly longer than wide, opening rounded and margins with fold with each a small posterior slit; cheliceral claw with ten denticles. In addition to the species description, we have included a key for identifying Charinus species in Brazil, along with a distribution map that highlights the known species in the country. This newly described species marks the first formal documentation of a Charinus species within the state of Tocantins. With the addition of this species, the global tally of recognized Charinus species now stands at 98, and Brazil, in particular, is home to a total of 44 formally described species within this genus.